PENINGKATAN KETERAMPILAN MEMBACA DONGENG MELALUI METODE SCRAMBLE KALIMAT PADA TEMA KEBERSAMAAN KELAS II SD MUHAMMADIYAH BAYAN TA. 2021/2022 - Ikne Sabela; Arum Ratnaningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
“Improving Fairytale Reading Skills Through the Sentence Scramblel Method on the Theme of Togetherness for Class II SD Muhammadiyah Bayan TA. 2021/2022". Elementary School Teacher Education, FKIP, Purworejo Muhammadiyah University, 2022. This study aims to: 1) describe the application of fairy tale reading skills through the sentence scramble method for second grade students at Muhammadiyah Bayan Elementary School, 2) find out the improvement of fairy tale reading skills with the scramble method. sentence on the theme of togetherness of class II students at SD Muhammadiyah Bayan. The type of research used in this research is Classroom Action Research (CAR) which is carried out in two cycles, each cycle having two meetings. The research subjects are second grade students of SD Muhammadiyah Bayan TA. 2021/2022 with a total of 26 students. Data collection techniques in this study used interviews, observations, tests, field notes and documentation. The results showed that there was an increase in fairy tale reading skills through the sentence scrambel method for students who achieved the average in the pre-cycle the percentage of learning outcomes was only 34.61% in the first cycle, 50.00% in the second cycle, reaching 84.61%. The results of the observation of student activities also experienced an increase. In the first cycle, 63.75% increased to 81.15% the increase in fairy tale reading skills based on the average increase in aspects of accuracy, pronunciation, intonation, fluency and clarity of voice. It can be concluded that the sentence scramble method can improve the reading skills of the second grade students of SD Muhammadiyah Bayan.